A re-evaluation of Holocene relative sea-level change along the Fujian coast, southeastern China - Yu, Fengling (2023)
The southeastern China coast is a region of special interest in the study of past and present relative sea-level change, given its distal location from giant ice sheets (far-field regions). During the past decades, a large number of biological, geological, and archaeological sea-level indicators have been retrieved from the Fujian coastal region which allows for recalibration and recalculation of sea-level index points (SLIPs). This study constructs a database of Holocene relative sea-level (RSL) observations for the Fujian coast, southeastern China. The database contains 59 quality-controlled SLIPs which show that RSL for the Fujian coast did not exceed present (0 m) during the Holocene, except potentially during 7.5–5.5 cal. kyr BP and 1.8–0.7 cal. kyr BP. Rates of RSL change were highest during the early Holocene and have decreased over time, due to the diminishing response of the Earth's mantle to glacial isostatic adjustment (GIA) and reduction of meltwater input. A series of sea-level oscillations were recorded in our SLIPs-based reconstructions which might correspond to global climate warming or cooling events. We assessed the spatial variability of RSL histories and compared these with the ICE-6G_C and ANU-ICE GIA model predictions. Substantial misfits between GIA predictions and regional RSL reconstructions were recognized: (1) the deceleration of the early-Holocene sea-level rise ended about one millennia earlier in the ICE-6G_C model than in the SLIPs-based reconstructions; (2) GIA model predictions show a mid-Holocene sea-level highstand of 1–3 m which is absent from our SLIPs-based reconstructions; and (3) all GIA model predicted a gradual RSL fall to 0 m since the middle Holocene, while our reconstruction displays significant RSL oscillations. It is presently unknown whether these misfits are caused by uncertainties in regional tectonic movement estimation or parameters used in the GIA models. Future applications of spatiotemporal statistical techniques are required to better quantify the gradient of the isostatic contribution and to provide improved context for the assessment of the ongoing acceleration of sea-level rise.